Analysis of Application Possibilities of RFID Technology in Road Transport - Neumann, T. (Scientific Journal of Gdynia Maritime University, 2017)
The paper presents examples of practical use of RFID technology in road transport and there are also proposed solutions to help manage the transport process. The principles of operation of these systems have been discussed and the benefits of using them have been demonstrated.